POTENSI EKSTRAK BUAH BELIMBING WULUH (Averrhoa Blimbi L.) SEBAGAI ANTIHIPERGLIKEMIA PADA HEWAN MENCIT SWISS WEBSTER - Ika Kurnia (JURNAL FARMASI GALENIKA, 2014)
Antihyperglicemia activity tests were conducted for Averrhoa bilimbi L. fruit extract in male Swiss Webster mice using glucose tolerance tests. This study aimed to determined the effect of Averrhoa bilimbi L. fruit extracts using 3 different types polarity of solvent, namely n-hexane, ethyl acetate and ethanol on blood glucose levels of mice were loaded with 50% glucose solution. Test animals were randomly divided into 12 groups: group 1 (normal group received the drug carrier), group 2 (the positive group received drug carrier), group 3 (glibenclamide 0.65 mg / kg bw), group 4-12 were test group received the extract n-hexane, ethyl and ethanol of Averrhoa bilimbi L. fruit extracts each dose of 5, 500, and 750 mg / kg bw respectively. Blood glucose levels were measured every 30 minutes for 120 minutes. The results showed that the ethanol extract of Averrhoa bilimbi L. fruit extracts doses of 5, 500 and 750 mg / kg bw showed the best antihiperglikemia activity.Based on the resultsof this study concludedthatAverrhoa bilimbi has antihyperglycemic activity.